Pengaruh Celebrity Endorser dan Brand Awareness terhadap Keputusan Pembelian pada Aplikasi Shopee di Kalangan Generasi Z - Khofifah; Nurul Sriminarti (Universitas Muhammadiyah Jakarta, 2026)
Digital transformation has accelerated since the COVID-19 pandemic, which imposed social restrictions and ecouraged a shift from traditional shopping patterns to online shopping. The increasing number of e-commerce users includes Generation Z, who represent the dominant consumer segment. Among various e-commerce platforms, Shopee has become the most frequently accessed application in indonesia. this study aims to examine and analyze the influence of celebrity endorser and brand awareness on purchase decisions on the Shopee application among Generation Z. although Shopee implements various marketing strategies to encourage purchase decisions, this study is limited to two variables, namely celebrity endorser and brand awareness. The sampling technique used was non-probability sampling with a purposive sampling approach. Data were collected through the distribution of questionnaires to Generation Z respondents (17-28 years), domiciled in Jabodetabek, who had made purchases on the Shopee application and had been exposed to advertisements or promotions involving celebrity endorser. The data analysis methods employed included validity testing, reliability testing, classical assumtion testing, multiple linear regression analysis, and coefficient of determination (R2) analysis to test the research hypotheses. The results indicate that celebrity endorser has a positive but insinificant effect, while brand awareness has a positive and significant effect on purchase decisions.